Avaliação de programas de secagem para madeiras de eucalipto elaborados com base em testes prévios a alta temperatura - Susin, Felipe (2013)
The difficulty of obtaining dry wood with a low incidence of defects is a challenge when it comes to eucalyptus wood, since the species of this genus exhibit drying difficult and high expression of defects, contributing to their use is limited and the level of losses on many occasions raised. The main objective of this study was to develop and evaluate programs for drying wood Corymbia citriodora, Eucalyptus robusta and Eucalyptus saligna. For this, it was evaluated drying parameters and physical characteristics of the species in preliminary tests, using equations to establish the drying programs for each species. Underwent two batches of 32 tablets with 270,0 x 15,0 x 2,5 (length, width and thickness), respectively, of each kind, drying using the same drying program for each species. For each batch, we used four control samples to monitor the moisture content and four boards for the evaluation of moisture gradients during drying and standardization phase. The programs were evaluated for drying the drying rate, the manifestation of defects, the final moisture content, the shrinkage, moisture gradient and the standardization phase. The drying rate in the application of drying programs maintained the trend presented during the preliminary assessment, with values equal to 5,38 x10-4, 1,10 x10-3 e 7,96x10-4 g/cm³.h for Corymbia citriodora, Eucalyptus robusta and Eucalyptus saligna, respectively. For the final moisture content, the three species showed variation satisfactory, and the Corymbia citriodora showed less dispersion between the parts, followed by Eucalyptus saligna and Eucalyptus robusta. The qualitative assessments showed that the wood, in general, the species which obtained the best results was Corymbia citriodora, followed by Eucalyptus saligna robust and Eucalyptus. The same trend was observed for the contractions during drying was not observed for the species difference between the coefficient anisotropic. The time used for the standardization step is only sufficient for Eucalyptus robusta, the moisture content which presented below 4% after the end of the standardization.